The impact of spiritual care for families at end-of-life in Intensive Care: An integrative review - Muldowney, Yvonne (My University, 2019)
Background: In intensive care end-of-life frequently includes or is closely witnessed by family members. Internationally while spiritual care of patients forms part of comprehensive patient-centred care, and is incorporated into quality and professional standards worldwide, families’ particular needs in this regard are not well understood. Aim: To identify and synthesise existing evidence related to families’ experience of spirituality having been part of end-of-life care in Intensive Care Units (ICU). Search and review methodology: PubMed, CINAHL, PsycINFO, Embase, AME, ASSIA, Google Scholar and Cochrane library were searched in 2018, yielding 53 articles. Key words used were ‘Critical Care’, ‘End-of-Life-Care’, ‘Spirituality’, Terminal care”, ‘Palliative care’ ‘Death’ and ‘Dying’. A combination of these terms using Mesh and Boolean operators ‘or’ or ‘and’ were used. Following the use of an inclusion/exclusion criteria twenty-nine papers were deemed suitable. Ethical approval was not required. To interpret the data and identify patterns thematic analysis was performed. Findings: Three recurring key themes emerged: spiritual care practices, value of chaplains and spiritual distress. Conclusions and implications: Death in the ICU is always tragic for the families. Quite frequently these deaths are unexpected, or occur after sudden traumatic events or prolonged illness. The effects of this, and the industrial type ICU environment, are not always conducive to a good death. While the need to provide spiritual care to patients and families is recommended at policy level internationally there is little overall standardisation of the nurses’ role in spiritual care in ICU, particularly in relation to the family. The family suffer from spiritual distress; nurses are often unprepared to address this. Families view spiritual care support received from nurses and healthcare chaplains positively. In light of this review it is recommended that ICU nurses incorporate spiritual care into their daily practice, greater collaboration between chaplains and clinicians, and further research to increase understanding of how ICU patients’/family needs can be met.
5th International Spirituality in Healthcare Conference
PUBLISHED
Trinity College Dublin
Keywords: Spiritual care; End-of-life; Chaplains; Spiritual distress; Intensive care units; Inclusive Society; Critical Care; Critical Care Nursing; Other; Health